Pembuatan Abstrak Indikatif Tugas Akhir Mahasiswa Program Studi Ilmu Informasi Perpustakaan dan Kearsipan Tahun 2006 - Maysuri, Siti; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This paper aims to describe the manufacture of final project abstract indicative of Information Science student of Library and Archives at the Library of the State University of Padang . In order for the final project can be used optimally , made ​​an indicative abstract . Indicative abstracts can be used as a search tool and a guideline Final searchers choose the final project you want to read . The method used in this research is descriptive . Data obtained from direct observation to Padang State University library . From the results obtained literature abstracts final assignment of the year 2006, as many as 30 titles.